The influence of infrastructure, environment and destination Attractiveness toward tourist intention to sabah. - Anis Nadira Yahazir; Anis Syuhadah Ishak; Aqilah Nadhirah Sukarno; Aree Suwanchatri A/P Ah Doong (2023)
This study aims to examine the effect of influence, environment and destination attractiveness toward visiting Sabah, study of domestic tourists. A total of 384 respondents consisting of citizens who have and have never visited Sabah were selected in this study using a quantitative approach. The findings of this study showed the infrastructure, environment, and destination attractiveness are the significant factors that encourage domestic tourists visiting Sabah. Furthermore, the findings of the study extended the knowledge of tourist preferences within the context of the tourism industry in general and Malaysia.